Development and Testing of an Anxiety Model in Elementary School Students Based on Executive Functions and the Parent/Child Relationship: Mediating Role of Emotion Regulation - Salar Mohamadi Bolbanabad; Nooshin Taghinejad; Azita Amirfakhraei (Iranian Journal of Educational Research)
Objective: This study aimed to develop and test a model of anxiety in elementary school students based on executive functions and the parent-child relationship, considering the mediating role of emotion regulation. Methods: The research employed a correlational descriptive method. The sample size consisted of 336 participants selected through multi-stage cluster random sampling, and they completed standard questionnaires including the Spence Children's Anxiety Scale (2003), Barkley's Deficits in Executive Functioning Scale for Children and Adolescents (2012), Fine and colleagues' Parent-Child Relationship Scale (1983), and the Emotion Regulation Checklist for Children and Adolescents (2003). Data analysis was conducted using structural equation modeling in the AMOS software. Results: The findings indicated that the research structural model fit the collected data. Executive functions were positively and significantly related to anxiety (p = 0.001, β = 0.284). The parent-child relationship was negatively and significantly associated with anxiety (p = 0.001, β = -0.414), teacher-student interaction was positively and significantly related to anxiety (p = 0.001, β = 0.371), and the factor of emotion regulation reappraisal had a negative relationship, while the factor of emotion regulation suppression had a positive and significant relationship with elementary school students' anxiety. Moreover, the factors of suppression and reappraisal of emotion regulation mediated the relationship between executive functions and anxiety (p = 0.001, β = 0.112), mediated the negative and significant relationship between the parent-child relationship and anxiety (p = 0.001, β = -0.140), and mediated the positive and significant relationship between teacher-student interaction and anxiety (p = 0.001, β = 0.122) in elementary school students. Conclusions: Based on the findings of the current study, it has been determined that both executive functions and the parent-child relationship have a direct and indirect impact on children's anxiety levels through emotion regulation.